Endocrine disruptors affect the expression of estrogen receptor genes and proteins in the white cloud mountain minnow Tanichthys albonubes (Teleostei: Cyprinidae) - Ke, Chen; Meilin, Chen; Guangzhi, Ma; Yuqin, Fan; Lin, Liu; Weiting, Chen (Frontiers in Physiology, 2022)
The endocrine disruptor chemicals (EDCs) are ubiquitous in the environment, and it has raised wide public concern because of the dangers of EDCs for living organisms and the environment. In order to comparatively study the effects of EDCs [17-α-ethinylestradiol (EE2), Bisphenol A (BPA) and Nonylphenol (NP)] on the expression of estrogen receptors (ERs: erα, erβ1, and erβ2) at mRNA and protein level, total 520 adult Tanichthys albonubes were exposed to E2, EE2, BPA and NP with three concentrations respectively: EE2 (1, 5, 25 ng/l), NP (10, 50, 250 μg/l), BPA (100, 500, 2,500 μg/l) for 28 days, E2 (2, 20, 200 ng/l) being as the positive control. After treatment, the brain, eye, gill, heart, liver, gut, kidney, muscle, testis, and ovary were collected, following by the real-time quantitative PCR (RT-qPCR) and western blot methods to detect the expression levels of erα, erβ1, and erβ2 in T.albonubes at mRNA and protein level. Our results showed that high expression of terα (t means T.albonubes), terβ1, and terβ2 were detected in liver, while terβ1 and terβ2 mainly expressed in the liver, intestine, kidney, muscle and testis. EE2, BPA, and NP treatment all up-regulated the expression of terα, terβ1, and terβ2 in the brain, liver, and testis, but with some variations. Similar to mRNA level, both TERα and TERβ were up-regulated by all the EE2, BPA, and NP treatment with dose-dependent effect. In conclusion, the responses of ERs of T.albonubes to the EDCs present measurability and susceptibility, which make it possible for T. albonubes to be an efficient biomarker to monitor and evaluate the pollution of endocrine disrupting chemicals in water environment.